Nurses' exposure to verbal abuse at a university hospital in Crete, Greece - Nikos Rikos; Demetra Telli; Athanasia Hatzinikolaou; Demetra Mantikou; Michael Rovithis; Maria Fourmouzi; Manolis Linardakis (Tehran University of Medical Sciences, 2021)
Background & Aim: The current study aimed to investigate workplace bullying, specifically verbal abuse of working nurses, and its consequences on the physical and psychological levels. Methods & Materials: A cross-sectional study was designed and implemented in 151 nurses working at a university hospital. The survey was conducted in 2018 at a university hospital in Greece, and the Verbal Abuse Scale (G-AVQ v.0/2015) was used to assess the verbal abuse level. Multiple linear regression analysis was applied, and distributions were tested for their symmetry using Blom's method (QQ plot). Results: 88.1% were women as the mean age of all was 41.7 years and 16.1 years the mean length of employment. Almost all nurses (94.7%) reported experiencing verbal abuse, as 77.6% reported that the perpetrator was a patient's relative (p<0.05). Among Cognitive Assessment, Coping, Severity of Effects, and Strength of Feeling, Coping had the highest mean value the highest mean value, while Severity of Effects had the lowest (2.52 vs. 1.83, p<0.05). Multiple linear regression analysis showed that frequency of verbal abuse type has a significant correlation with higher Coping (β=0.28, p=0.007) and Strength of Feeling values (β=0.29, p=0.010). Similarly, the severity of verbal abuse type has a significant correlation with higher Strength of Feeling values (β=0.30, p=0.014). Conclusion: Almost all the nurses reported experiencing verbal abuse as the 'patients' relatives were the main perpetrators. Although the nurses seem to cope with verbal abuse successfully, this fact is described as stressful. Moreover, the frequency, severity of verbal abuse, and consequences are correlated to the emotions that arise from it.